Serum Creatine Kinase as a Biomarker to Predict Wooden Breast in vivo for Chicken Breeding - Kong, Fuli; Zhao, Guiping; He, Zhengxiao; Sun, Jiahong; Wang, Xicai; Liu, Dawei; Zhu, Dan; Liu, Ranran; Wen, Jie (Frontiers in Physiology, 2021)
The present study aimed to find a blood marker for the prediction of wooden breast (WB) and white striping (WS) to assist the genetic selection of fast-growing chickens. The experiments were carried out with two chicken flocks: 150 male broilers in flock 1 and 100 male and female broilers in flock 2. Both flocks were slaughtered and measured. The breast fillets were assessed by combining subjective scoring and compression force at 28 (flock 1 only) and 42 days old. The enzyme activity in serum and breast tissue (flock 1 only) of normal and moderate affected groups was tested. The results showed that the compression force was significantly different between the normal and affected groups at 28 and 42 days (P<0.001), and it increased significantly with rising WB and WS scores. The serum creatine kinase (CK) value increased significantly with rising compression force at 42 days old (P<0.001). The serum CK positively correlated with compression force (r=0.608; P<0.001) and could be used as a biomarker to predict the degree of WB and WS in live birds. The association between serum CK and compression force is consistent between flocks 1 and 2. In conclusion, our study indicated that compression force could be an objective indicator to differentiate breast fillets and serum CK could be a candidate biomarker to predict WB and WS and assist genetic selection in fast-growing broiler breeding.